Protective Effects of Teucrium Polium Leaf Ethanolic Extract Against Nicotine-Induced Nephrotoxicity in Mice. - ALATAWI, Afaf; MAODAA, Saleh; ALARIFI, Saud; HARRATH, Abdel Halim; AL-SHAEBI, Esam M.; ALHOMOUD, Dalal A.; ALAWWAD, Sarah A.; AJAREM, Jamaan S. (Physiological Research, 2025)
This study aimed to examine the protective and antioxidant properties of a Teucrium polium leaf extract against acute kidney damage caused by nicotine in male mice. A total of 24 male Swiss albino mice were divided into four groups. The control group (oral solution of 0.9 % NaCl), the positive control group (injections of nicotine at a dosage of 2.5 mg/kg b.w.), the third group (received 100 mg/kg b.w. ethanolic extract of T. polium), and the fourth group (nicotine injections at a dosage of 2.5 mg/kg b.w + 100 mg/kg b.w. ethanolic extract of T. polium). GC-MS analysis of the plant extract revealed the presence of 16 active compounds. Nicotine administration resulted in a significant increase in kidney biomarkers, namely urea, uric acid, and creatinine, by 50 %, 207 %, and 129 %, respectively, compared to the control group, indicating nephrotoxicity. However, treatment with the T. polium extract improved these parameters by 77 %, 79 %, and 83 %, respectively. Furthermore, the nicotine group exhibited elevated levels of nitric oxide (NO) and malondialdehyde (MDA), which are indicators of oxidative stress, as well as decreased levels of glutathione (GSH) and reduced activity of superoxide dismutase (SOD). Conversely, the administration of the T. polium extract reversed these effects, suggesting its potential to enhance the antioxidant defense system. This finding was also supported by the improvements observed in the kidney TUNEL assay sections and the preservation of histopathological integrity. In conclusion, the T. polium extract demonstrates protective effects against nicotine-induced kidney damage by modulating oxidative stress and antioxidant defense mechanisms.